The Challenge of Formulating State Administration as a Discipline in the Perspective of Public Management - Sri Yulianty Mozin; Alexander H. Badjuka; Nahla Nafilah Lahay; Joevanka Teressa Waworuntu; Nur Fadillah Rasjid; Rizki A. Mohi (Universitas Muhammadiyah Palu, 2026)
This study examines the epistemological challenges in defining Public Administration as an independent discipline amid the dominance of contemporary Public Management paradigms. Since the rise of New Public Management (NPM) and New Public Governance (NPG), the discipline has faced an identity crisis concerning its academic legitimacy and conceptual boundaries. Using a qualitative-descriptive approach, this paper analyzes the paradigm shift of Public Administration in Indonesia and its implications for academic orientation and governance practices. The findings reveal that Indonesia's Public Administration faces challenges at three levels: ontological (the shift from state administration to managerial governance), epistemological (disciplinary legitimacy crisis), and axiological (value transition from public ethics to efficiency). To address these issues, it is necessary to recontextualize Public Administration as a value-driven discipline rooted in public interest, social justice, and civic responsibility. Such an approach would restore the normative foundation of Public Administration while maintaining its relevance alongside Public Management in contemporary governance systems.